John Haywood, A Manual of the Laws of North-Carolina 234-35 (1814) - (:unkn) unknown (My University, 1784)
Hunting, § 3: If any person or persons shall be discovered hunting in the woods with a gun, in the night time, by fire light, such person or persons so offending shall, upon conviction, by indictment or presentment in any court of record in this state, be fined by such court 20 current money, to be applied to the use of the county wherein the offence was committed until all costs accruing upon the presentment be paid.
Keywords: HUNTING REGULATION